Age and prostate volume are risk factors for transient urinary incontinence after transurethral enucleation with bipolar for benign prostatic hyperplasia. (3rd October 2017) - Hirasawa, Yosuke; Kato, Yuji; Fujita, Kiichiro
Abstract : Objectives: To investigate the predictive factors for transient urinary incontinence after transurethral enucleation with bipolar. Methods: We retrospectively analyzed the data of 584 patients who underwent transurethral enucleation with bipolar between December 2011 and September 2016 operated by a single surgeon. Urinary incontinence after transurethral enucleation with bipolar was defined as involuntary leakage of urine that required the use of pads. It was evaluated at 1 week, and 1, 3, 6, 12 and 24 months after transurethral enucleation with bipolar. We defined transient urinary incontinence as urinary incontinence persisting up to 1 month after transurethral enucleation with bipolar. Based on independent risk factors identified by a multivariate stepwise logistic regression analysis, a nomogram to predict transient urinary incontinence was developed. Results: Of the 584 patients, 17.3%, 13.5%, 3.1%, 0.41%, and 0% patients had urinary incontinence at 1 week, 1, 3, 6 and 12 months after transurethral enucleation with bipolar, respectively. The mean (±standard error) age was 69.6 ± 0.26 years, estimated prostate volume was 54.7 ± 0.91 cm 3, operative time was 58.0 ± 1.1 min and the prostate specimen weight was 30.6 ± 0.69 g. On univariate analysis, age, prostate volume estimated by transrectal ultrasonography, prostate‐specific antigen, prostate specimen weight, operative time, prostate specimen weight/prostate volume and prostate specimen weight/operative time were significant predictive factors for transient urinary incontinence after transurethral enucleation with bipolar. On multivariate analysis, age (hazard ratio 1.07, P ‐value = 0.0034) and prostate volume (hazard ratio 1.03, P ‐value < 0.0001) were independent risk factors for transient urinary incontinence after transurethral enucleation with bipolar. Conclusions: Age and prostate volume estimated by transrectal ultrasonography seem to represent significant independent risk factors for transient urinary incontinence after transurethral enucleation with bipolar. This should be well discussed with the patient before surgery.